1972
DOI: 10.1177/070674377201700604
|View full text |Cite
|
Sign up to set email alerts
|

Lowering the Cost of Psychiatric Care

Abstract: This paper reports a four-year experience and includes follow-up data from the operation of a novel inpatient general hospital unit. The two main features of the unit are: a relatively brief duration of hospitalization; and the employment of nursing staff as therapists in exactly the way residents are usually used. The inpatient stay is considered to be a special opportunity for organizing important changes in the life styles and living arrangements of patients. It is also a time for making careful observatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1974
1974
1983
1983

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Climent and his colleagues (1978), in a small study of an emergency out-patient service in Colombia, discovered that auxiliary psychiatric nurses were clinically more effective and less expensive than psychiatrists. A limited analysis of the costs of psychiatric nurse therapists in Canada also indicated that the margin of advantage accrued to nursing (Smith, 1972). In Britain, Ginsberg & Marks (1977), in an uncontrolled study of nurse behaviour therapists, found that patients made fewer claims on health care resources and on the worktime of their relatives in the year after therapy than in the year before.…”
Section: Discussion Previous Studiesmentioning
confidence: 99%
“…Climent and his colleagues (1978), in a small study of an emergency out-patient service in Colombia, discovered that auxiliary psychiatric nurses were clinically more effective and less expensive than psychiatrists. A limited analysis of the costs of psychiatric nurse therapists in Canada also indicated that the margin of advantage accrued to nursing (Smith, 1972). In Britain, Ginsberg & Marks (1977), in an uncontrolled study of nurse behaviour therapists, found that patients made fewer claims on health care resources and on the worktime of their relatives in the year after therapy than in the year before.…”
Section: Discussion Previous Studiesmentioning
confidence: 99%